Formaldehyde-free adhesive for single-component plywood and application of formaldehyde-free adhesive

By using formaldehyde-free adhesive for single-component plywood, combined with water-soluble acrylic resin, fillers and polyol curing agents, the problems of inconvenient preparation and short application period are solved, and the flexibility and cost-effectiveness of plywood production are improved. , ensuring glue strength and safety.

CN119264842APending Publication Date: 2025-01-07JIANGSU AKST NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411391060.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing formaldehyde-free adhesive is a two-component system, which has problems such as inconvenient formulation, short application period, short opening time and material accumulation loss, making it difficult to meet the flexibility and cost requirements of plywood production.

Method used

Using formaldehyde-free adhesives for single-component plywood, including water-soluble acrylic resin, fillers, thickeners and polyol curing agents, the cross-linking curing reaction under hot pressing conditions forms a thermosetting resin with superior bonding performance, which is suitable for strict Harsh single-sided glue coating process.

Benefits of technology

It realizes long opening time and long application period of adhesive, improves transfer rate and glue strength, reduces costs, and ensures safe, environmentally friendly and non-toxic plywood production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005072436120000071
    Figure BDA0005072436120000071
  • Figure BDA0005072436120000081
    Figure BDA0005072436120000081
  • Figure FDA0005072436010000011
    Figure FDA0005072436010000011
Patent Text Reader

Abstract

The invention provides a formaldehyde-free adhesive for single-component plywood and application of the formaldehyde-free adhesive, and relates to the field of high polymer materials. The formaldehyde-free adhesive comprises water-soluble acrylic resin, a filling agent, a thickening agent, a polyol curing agent and water, the polyol curing agent is a compound containing at least two hydroxyl groups. The formaldehyde-free adhesive for the single-component plywood does not contain isocyanate and other curing agents with high activity, the single-component adhesive prepared by adding the polyol curing agent is long in pot life and lasting in performance, the pot life is larger than or equal to 6 months, the bonding strength is larger than or equal to 0.7 MPa after hot water boiling, the opening time is larger than or equal to 6 h, and the transfer rate is larger than or equal to 90%; the adhesive is far better than an emulsion type formaldehyde-free adhesive and a double-component adhesive in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer materials, and in particular to a formaldehyde-free adhesive for single-component plywood and an application thereof. Background Art

[0002] Plywood is a three-layer or multi-layer board material made by peeling wood segments into veneers or planing wood blocks into veneers, and then gluing them with adhesives. Currently, the adhesives used in plywood are mainly formaldehyde-based adhesives. Due to their high cost-effectiveness, they are widely used in plywood production. However, formaldehyde-based adhesives contain a large amount of free formaldehyde, which leads to serious excess of free formaldehyde in indoor air. With people's attention to indoor environmental pollutants and their own health, as well as the upgrading of the wood processing industry, the use of formaldehyde-free adhesives to produce plywood has become a research hotspot in recent years.

[0003] Patent CN 114539973 A discloses an adhesive for formaldehyde-free plywood, a preparation method and its application, using 25wt% polymethylene polyphenyl isocyanate PM400, 6wt% low-viscosity cellulose HX400, 1.5wt% sericite powder, 2wt% dipropylene glycol butyl ether, 10wt% flour, 3wt% calcium carbonate, 0.03wt% fungicide KORDEX, and 52.47wt% process water in percentage. Patent CN 111918945A discloses a formaldehyde-free adhesive composition with excellent water resistance, which comprises: (a) an aqueous emulsion of an acrylic polymer; and (b) an aliphatic isocyanate crosslinker; wherein the acrylic polymer has at least one structural unit, the structural unit has at least one heterofunctional group of one or more ethylenically unsaturated monomers, and the acrylic polymer has a glass transition temperature of -45°C to 0°C. The patent uses boiling water for 4 hours, drying in a 63°C air convection drying oven for 20 hours, and boiling in boiling water for 4 hours to test its bonding strength, with the highest being 1.1MPa. In addition, the formula uses a less active aliphatic isocyanate crosslinker, which can achieve a workable period of about 4 hours, but its opening time is not long, and the opening time cannot reach ≥6 hours.

[0004] The above-mentioned formaldehyde-free adhesives are all two-component adhesives, in the form of component A + component B with higher activity, which are mixed and used on the production site. Usually, the curing agent belongs to the isocyanate system, which has high activity and will react with water when it encounters water. The application period of this two-component system glue is generally less than 4 hours, and this two-component glue has the following problems during use:

[0005] 1. The adhesive should be used immediately after preparation. If the production equipment stops temporarily due to a malfunction, the adhesive may become ineffective due to long storage time, which not only reduces the flexibility of continuous production, but also increases the cost of the manufacturer;

[0006] 2. Each time the adhesive is prepared, weighing and stirring operations are required, which not only has low batching efficiency, but also high labor costs;

[0007] 3. Frequent weighing and preparation of each component can easily lead to cumulative loss of materials.

[0008] Therefore, the development of a one-component formaldehyde-free adhesive for plywood, which can adapt to existing production equipment and conditions under the harsh process conditions of single-sided gluing, has a long opening time (opening time ≥ 6h), a long application period and is formaldehyde-free, is an issue that the entire industry urgently needs to solve. Summary of the invention

[0009] In view of the above problems existing in the prior art, the present invention provides a formaldehyde-free adhesive for a one-component plywood.

[0010] The one-component formaldehyde-free adhesive for plywood of the present invention comprises a water-soluble acrylic resin, a filler, a thickener, a polyol curing agent and water; the polyol curing agent is a compound containing at least two hydroxyl groups. The one-component formaldehyde-free adhesive undergoes a cross-linking curing reaction under a hot pressing condition of 120-200° C., and becomes a thermosetting resin with excellent bonding performance.

[0011] In one embodiment of the present application, the one-component formaldehyde-free adhesive for plywood of the present invention comprises, based on 100 parts by weight, 10 to 50 parts of a water-soluble acrylic resin, 5 to 40 parts of a filler, 0.5 to 5 parts of a thickener, 5 to 25 parts of a polyol curing agent and the remainder water.

[0012] In one embodiment of the present application, the polyol curing agent is β-hydroxyalkylamide, 1,2-ethylene glycol, 1,3-propylene glycol, diethylene glycol, 1,4-butanediol, 1,2,3-cyclohexanetriol, 1,2,4-butanetriol, 1,2,3-butanetriol, 1,2,5-pentanetriol, glycerol, glycerol polyether polyol, 2,2-dimethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 2-methyl-2,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 2-ethyl-1,3-hexanediol, 2-hydroxymethyl-2-methyl-1,3-propanediol, 2-ethyl-2- Hydroxymethyl-2-methyl-1,3-propanediol, 1,2,6-hexanetriol, 2,2-dihydroxymethyl-2,3-propanediol, pentaerythritol, trimethylolpropane, glucose, fructose, sorbitol, sucrose, mannitol, maltose, maltitol, glucose, resorcinol, catechol, pyrogallol, 1,2-ethylene glycol dimer, 1,2-ethylene glycol trimer, 1,2-propylene glycol, 1,2-propylene glycol dimer, 1,2-propylene glycol trimer, ethanolamine, isopropanolamine, diethanolamine, diisopropanolamine, triethanolamine, homopolymer of hydroxyethyl (meth)acrylate, copolymer of hydroxyethyl (meth)acrylate, homopolymer of hydroxypropyl (meth)acrylate, copolymer of hydroxypropyl (meth)acrylate or polyvinyl alcohol, more preferably, the polyol curing agent is β-hydroxyalkylamide.

[0013] The β-hydroxyalkylamide is shown in Formula I:

[0014] Wherein, R is methyl or hydrogen, and m=2-8.

[0015] Further, m is preferably 4, and the selected β-hydroxyalkylamides include but are not limited to N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, N,N,N',N'-tetrakis(2-hydroxypropyl)adipamide, and the like.

[0016] The water-soluble acrylic resin is a water-based high molecular polymer obtained by solution polymerization of a vinyl-containing unsaturated carboxylic acid monomer and a hydrophobic functional monomer in an aqueous solution. No emulsifier is added to the water-soluble acrylic resin. The water-soluble acrylic resin has a molecular size of ≤1 nm. The number average molecular weight of the water-soluble acrylic resin is 2000-30000. More preferably, the number average molecular weight of the water-soluble acrylic resin is 8000-25000. The number average molecular weight of the present invention is obtained by gel permeation chromatography (GPC) testing.

[0017] It should be noted that the single-sided gluing described in this patent has a specific meaning, that is, between two bonding substrate veneers, only one side has a glue layer. There are two ways of single-sided gluing in actual production. For example, for the production of 7-layer plywood, the veneers after assembly are numbered 1-7 from bottom to top, and each layer of veneer is provided with an upper layer and a lower layer. One way of single-sided gluing is to use a single-roll gluing machine to apply glue. After 1, 2, 3, 4, 5, and 6 layers of veneers pass through the single-roll gluing machine, the upper layer of each veneer is coated with glue. After the 7th veneer is covered on the 6th veneer after vertical and horizontal assembly, there are a total of 6 layers of glue. The second way of single-sided gluing is to use a double-roll gluing machine. After the 2nd, 4th, and 6th veneers pass through the double-roll gluing machine, both the upper layer and the lower layer are coated with glue, while the 1st, 3rd, 5th, and 7th veneers do not need to be coated with glue. The double-sided glued and un-glued veneers are cross-assembled to obtain plywood, with a total of 6 layers of glue. The final gluing state of these two methods is that there is only a glue layer on one side between two bonding substrates. This is the most commonly used and common production process for producing plywood. If you want to ensure that the adhesive can be evenly distributed on any surface layer of the veneer, you can also use a double-roller glue coater to coat both sides of veneers No. 2, 3, 4, 5, and 6, and use a single-roller glue coater to coat one side of veneers No. 1 and 7. The actual number of glue layers is 12. The production efficiency of this method will drop by one-half or more, and the amount of glue needs to be increased by 70-100% (because there is a minimum amount of glue in the gluing process of the veneer), which greatly increases the cost. Therefore, most plywood production is carried out by single-sided gluing, which requires that the adhesive has a sufficient transfer rate between adjacent veneers to ensure the performance of the plywood. The following plywood production processes described in this patent are all single-sided gluing.

[0018] In one embodiment of the present application, the solid content of the water-soluble acrylic resin is 30% to 70%.

[0019] In one embodiment of the present application, the water-soluble acrylic resin monomer is an unsaturated carboxylic acid monomer containing a vinyl group.

[0020] In one embodiment of the present application, the vinyl-containing unsaturated carboxylic acid monomer is selected from one or more of acrylic acid, methacrylic acid, maleic acid, maleic anhydride, crotonic acid, isocrotonic acid, cinnamic acid, isocinnamic acid, oleic acid, 3-ethyl-3-butenoic acid, fumaric acid, butenoic acid, 2-methylmaleic acid, itaconic acid, and 2-methylitaconic acid.

[0021] In one embodiment of the present application, the amount of the hydrophobic functional monomer added is 10-35% of the total monomer addition amount. If the amount of the hydrophobic functional monomer added is too little, the water resistance cannot be significantly improved, resulting in the inability to significantly improve the immersion peeling performance and the bonding strength performance; if the amount of the hydrophobic functional monomer added is too much, the water solubility and stability of the product will be affected, and it is impossible to produce an acrylic resin that can be stably dissolved in water.

[0022] In one embodiment of the present application, the hydrophobic functional monomer can be selected from acrylic ester monomers, vinyl aromatic monomers, vinyl acetate monomers, vinyl monomers and other monomers that can participate in the polymerization reaction such as acrylonitrile or glycidyl (meth)acrylate.

[0023] In one embodiment of the present application, the acrylic acid ester monomer can be selected from methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, decyl acrylate, lauryl acrylate, methyl methacrylate, butyl methacrylate, isodecyl methacrylate or lauryl methacrylate.

[0024] In one embodiment of the present application, the vinyl aromatic monomer may be selected from styrene, α-methylstyrene, p-methylstyrene, ethylvinylbenzene, vinylnaphthalene, vinylxylene or vinyltoluene.

[0025] In one embodiment of the present application, the vinyl acetate monomer can be selected from vinyl acetate or vinyl butyrate; vinyl monomers, such as vinyl alcohol, vinyl chloride, vinyl toluene, vinyl benzophenone or vinylidene chloride.

[0026] In one embodiment of the present application, a filler may be added to the water-soluble formaldehyde-free adhesive. Adding the filler is beneficial to reducing the cost of the adhesive and improving its water resistance and strength.

[0027] In one embodiment of the present application, the filler is selected from one or more of bentonite, calcined kaolin, washed kaolin, calcium sulfate, talc, zeolite, mica powder, attapulgite, barium sulfate, quartz powder, and fumed silica.

[0028] In one embodiment of the present application, the filler may be selected from one or more of modified bentonite, calcined kaolin, and talc.

[0029] In one embodiment of the present application, the modified bentonite is sodium-based bentonite.

[0030] In one embodiment of the present application, the mesh size of the sodium bentonite is 600-1250 mesh, and the specific surface area is 400-800m 2 / g.

[0031] In one embodiment of the present application, a thickener can also be added to the formaldehyde-free adhesive for one-component plywood to increase the viscosity of the adhesive formula, so as to facilitate the coating and obtain the required amount of glue. The viscosity of the adhesive is preferably adjusted in the range of 6000 to 12000 cP. The viscosity of the present invention is measured by a rotational viscometer; the thickener is selected from one or more of anionic polyacrylamide thickeners, lithium magnesium silicate, xanthan gum, hydroxyethyl cellulose ether thickeners, sodium alginate, guar gum, bentonite, and non-ionic polyurethane rheology modifiers.

[0032] In one embodiment of the present application, the bonding strength of the formaldehyde-free adhesive for one-component plywood is ≥0.7MPa (eucalyptus); the applicable period of the formaldehyde-free adhesive for one-component plywood is ≥6 months; the opening time of the formaldehyde-free adhesive for one-component plywood is ≥6h; and the formaldehyde-free adhesive for one-component plywood has a transfer rate of ≥90%.

[0033] Furthermore, the method for preparing the formaldehyde-free adhesive for the one-component plywood of the present invention comprises the following steps:

[0034] Add water and water-soluble acrylic resin into a disperser respectively, stir for 5 to 10 minutes, add filler and thickener, stir for 20 to 25 minutes, add polyol curing agent, stir for 3 to 5 minutes, and obtain the one-component formaldehyde-free adhesive for plywood.

[0035] Furthermore, the method for preparing the formaldehyde-free adhesive for the one-component plywood of the present invention comprises the following steps:

[0036] Use glue coating equipment to coat one side of the single-component plywood with formaldehyde-free adhesive, with a single-side glue coating amount of 160-280g / m 2 ;

[0037] The glued veneers are assembled according to the principle that the fiber directions are perpendicular to each other to obtain assembled plywood;

[0038] After the plywood is stacked, it is cold pressed with a pressure of 0.5-1.2MPa and a time of 30-60min.

[0039] The cold pressed assembled board is hot pressed at a temperature of 140-170°C and a pressure of 0.7-1.5Mpa. The hot pressing time is calculated according to the thickness at 1min / mm. The formaldehyde-free plywood is obtained by curing for 48 hours.

[0040] Furthermore, the present invention provides an application of the one-component formaldehyde-free adhesive for plywood in the preparation of plywood.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. The formaldehyde-free adhesive formula for one-component plywood of the present application does not contain highly active curing agents such as isocyanate, but adds a polyol curing agent and is made into a single component, which has a long working life and can also solve the problem that the two-component adhesive in the prior art cannot be applied and has reduced performance due to the short working life;

[0043] 2. The water-soluble acrylic resin used in the one-component formaldehyde-free adhesive for plywood of the present application has a molecular size of ≤1nm and belongs to an aqueous true solution system. The drying process is a physical film-forming process without the presence of emulsion, which provides a very favorable basic condition for the penetration and transfer of the water-soluble formaldehyde-free adhesive;

[0044] 3. The present application adds 10-35% of hydrophobic functional monomers to the water-soluble acrylic resin to enable the adhesive to maintain a long opening time and applicability period, with an opening time of ≥6h, an applicability period of ≥6 months, and long-lasting performance, and a bonding strength of ≥0.7MPa after boiling in hot water;

[0045] 4. The one-component formaldehyde-free adhesive for plywood of the present application has a transfer rate of ≥90%, far exceeding the emulsion formaldehyde-free adhesive and two-component adhesive of the prior art;

[0046] 5. The raw materials of the formaldehyde-free adhesive used in the single-component plywood of the present application are formaldehyde-free, safe, environmentally friendly, non-toxic and harmless. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0048] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0049] In order to avoid the influence of the test environment and the moisture content of the single board substrate on the relevant test performance, the test environment of the relevant test methods below in this application is uniformly 25±2℃, 50±2% humidity, and the moisture content of the single board used is 10±2%.

[0050] The test method is as follows:

[0051] (1) Particle size test

[0052] The particle size test adopts the laser method, that is, the laser light scattering technology is used to characterize the particle size distribution of the particle sample, and the OMEC particle size tester is used. The particle size test range is 0.02μm-2000μm.

[0053] (2) Evaluation method of opening aging time

[0054] After the veneer is coated with glue, it is assembled vertically and horizontally according to the requirements to obtain assembled plywood. The amount of glue applied is 180-220g / m 2 ; Pre-press the assembled plywood in sequence to obtain pre-pressed boards; hot-press and cure the pre-pressed boards to obtain plywood samples, and saw the samples for immersion peeling and bonding strength tests; then calculate the open aging time: start timing from the veneer gluing to the end of pre-pressing of the assembled plywood, and at the same time meet the requirements that the plywood sample passes Class I immersion peeling test and the bonding strength is ≥1.0Mpa, this period of time is the open aging time.

[0055] (3) Stability test and shelf life test

[0056] 1) placing the adhesive at room temperature (23° C.) and observing the viscosity change of the adhesive at 0 months, 3 months, and 6 months, and observing whether there is deterioration such as stratification, precipitation, or flocculation;

[0057] 2) Place the adhesive in a high temperature (60° C.) environment and observe the viscosity change of the adhesive at 0 weeks, 3 weeks, 6 weeks and 12 weeks, and observe whether there is deterioration such as stratification, precipitation or flocculation.

[0058] Since the one-component adhesive of the present invention has a long applicable period, the present invention uniformly uses the stability test conditions under the above-mentioned room temperature (23° C.) environment as the applicable period of the adhesive of the present invention. Under this curing condition, the viscosity of the adhesive reaches twice the initial viscosity, and this time is the applicable period of the adhesive.

[0059] (4) Free formaldehyde test

[0060] Determine the free formaldehyde content according to 3.16 in GB / T14074-2017.

[0061] (5) Immersion stripping performance test

[0062] Eucalyptus veneer is used, the thickness of the veneer is 2.2mm, according to 180-220g / m 2The seven-layer veneer is assembled vertically and horizontally with a coating amount of glue, and single-sided glue is applied. After gluing, the opening is unified for 4 hours. After opening, cold pressing is carried out at a pressure of 0.8MPa for 60min, and then further hot pressing is carried out. The hot pressing pressure is 0.8Mpa, the hot pressing temperature is 160℃, and the hot pressing time is 15.4min calculated according to 1min / mm; after the hot pressing, the immersion peeling is carried out in accordance with 4.19.4.1 Class II test in GB / T 17657-2022, that is, the specimen is immersed in 63±3℃ hot water for 4h, and then taken out and dried in a drying oven at 63±3℃ for 3h, and the immersion peeling performance is observed.

[0063] (6) Bonding strength performance test

[0064] Eucalyptus veneer is used, the thickness of the veneer is 2.2mm, according to 180~220g / m 2 The seven-layer veneer is assembled longitudinally and horizontally with a coating amount and single-sided coating is carried out. After coating, the opening is unified for 4 hours. After opening, cold pressing is carried out at a pressure of 0.8MPa for 60min, and then further hot pressing is carried out. The hot pressing pressure is 0.8Mpa, the hot pressing temperature is 160℃, and the hot pressing time is 15.4min calculated according to 1min / mm. After hot pressing, the bonding strength is measured according to 4.17 of GB / T 17657-2022, and the immersion treatment of the specimen is carried out according to 4.17.4.2b) of GB / T 17657-2022, that is, hot water immersion: immersion in 63±3℃ hot water for 3h, and cooling at room temperature for 10min after taking out.

[0065] (7) Adhesive transfer rate test

[0066] 1) First, add 0.5% blue water-based color paste to the formaldehyde-free adhesive for one-component plywood and stir to mix evenly;

[0067] 2) Use glass rod to apply glue manually according to 180~220g / m 2 The amount of glue applied is applied on a single-layer wooden board of about 10cm×10cm;

[0068] 3) The single-layer wood board used is made of hard birch veneer, and the thickness of the veneer is 2.2mm;

[0069] After gluing, the opening time is uniformly set to 4h at room temperature. After the opening, take another un-glued birch veneer of the same area for cold pressing. The cold pressing pressure is 0.8MPa and the cold pressing time is 30min. Then, further hot pressing is performed. The hot pressing pressure is 0.8Mpa, the hot pressing temperature is 160℃, and the hot pressing time is 4.4min calculated according to 1min / mm.

[0070] 4) After the hot pressing is completed, use tools or other external forces to pry apart the bonding layers of the two layers of solid wood composite wood boards, and observe the percentage of the area where the adhesive in the coating layer has been transferred with the naked eye. The percentage represents the transfer rate of the adhesive. The larger the transfer area of ​​the adhesive, the greater the transfer rate. If there are individual batches of samples with strong adhesion that are difficult to pry apart, put the samples in hot water and boil them for 2 to 4 hours, then take them out and pry them apart, and then observe the transfer rate.

[0071] The specific implementation is as follows:

[0072] Example 1

[0073] The monomer composition of the water-soluble acrylic resin is: 90% acrylic acid, 10% hydrophobic functional monomer butyl acrylate; the number average molecular weight of the water-soluble acrylic resin is 4000; the solid content is adjusted to 50%. By weight, 50 parts of the water-soluble acrylic resin, 15 parts of kaolin, 1 part of xanthan gum, 25 parts of curing agent N,N,N',N'-tetrakis (β-hydroxyethyl) adipamide, and the rest of water are added and mixed evenly to obtain a single-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and applicability, and applied to plywood and tested for performance.

[0074] Example 2

[0075] The monomer composition of the water-soluble acrylic resin is: 75% acrylic acid, 25% hydrophobic functional monomer ethyl acrylate; the number average molecular weight of the water-soluble acrylic resin is 8000; the solid content is adjusted to 50%. According to weight, 50 parts of the water-soluble acrylic resin, 5 parts of kaolin, 1 part of xanthan gum, 13 parts of curing agent triethanolamine, and the rest of water are added and mixed evenly to obtain a single-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and applicability, and is applied to plywood and tested for performance.

[0076] Example 3

[0077] The monomer composition of the water-soluble acrylic resin is: 65% acrylic acid, 35% hydrophobic functional monomer methyl acrylate; the number average molecular weight of the water-soluble acrylic resin is 15000; the solid content is adjusted to 50%. According to weight, 50 parts of the above water-soluble acrylic resin, 15 parts of kaolin, 0.5 parts of xanthan gum, 20 parts of curing agent N,N,N',N'-tetrakis (β-hydroxypropyl) adipamide, and the rest of water are added and mixed evenly to obtain a single-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and applicability, and applied to plywood and tested for performance.

[0078] Example 4

[0079] The monomer composition of the water-soluble acrylic resin is: 65% acrylic acid, 35% hydrophobic functional monomer methyl acrylate; the number average molecular weight of the water-soluble acrylic resin is 28000; the solid content is adjusted to 50%. According to weight, 50 parts of the water-soluble acrylic resin, 40 parts of quartz powder, 2 parts of xanthan gum, 6 parts of curing agent glycerin, and the rest of water are added and mixed evenly to obtain a single-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and application period and applied to plywood for performance testing.

[0080] Example 5

[0081] The monomer composition of the water-soluble acrylic resin is: 90% acrylic acid, 10% hydrophobic functional monomer methyl acrylate; the number average molecular weight of the water-soluble acrylic resin is 25000; the solid content is adjusted to 50%. According to weight, 50 parts of the water-soluble acrylic resin, 29 parts of calcium sulfate, 5 parts of xanthan gum, 15 parts of curing agent trimethylolpropane, and the rest of water are added and mixed evenly to obtain a single-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and applicability, and is applied to plywood and tested for performance.

[0082] Example 6

[0083] The formula and process are the same as those in Example 3, except that the hot pressing temperature is 150°C.

[0084] Comparative Example 1

[0085] The ratio and composition of the remaining components are the same as those in Example 1, except that the curing agent is polymeric isocyanate (polymeric MDI), and the remaining water is added and mixed evenly to obtain a one-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and applicability, applied to plywood, and performance tested.

[0086] Comparative Example 2

[0087] The rest of the ratios and compositions are the same as those in Example 2, except that the curing agent is isophorone diisocyanate, and the rest is mixed with water to obtain a one-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and applicability, applied to plywood, and subjected to performance testing.

[0088] Comparative Example 3

[0089] The preparation is based on Example 3. The monomer composition of the water-soluble acrylic resin is: 95% acrylic acid, 5% hydrophobic functional monomer methyl acrylate; the number average molecular weight of the water-soluble acrylic resin is 15,000; the solid content is adjusted to 50%. By weight, 50 parts of the above water-soluble acrylic resin, 15 parts of kaolin, 0.5 parts of xanthan gum, 20 parts of curing agent N,N,N',N'-tetrakis (β-hydroxypropyl) adipamide, and the rest of water are added and mixed evenly to obtain a single-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and applicability, applied to plywood, and performance tested.

[0090] Comparative Example 4

[0091] The preparation is based on Example 3. The monomer composition of the water-soluble acrylic resin is: 95% acrylic acid, 5% hydrophobic functional monomer methyl acrylate; the number average molecular weight of the water-soluble acrylic resin is 15,000; the solid content is adjusted to 50%. By weight, 50 parts of the above water-soluble acrylic resin, 15 parts of kaolin, 0.5 parts of xanthan gum, 29 parts of curing agent N,N,N',N'-tetrakis (β-hydroxypropyl) adipamide, and the rest of water are added and mixed evenly to obtain a single-component formaldehyde-free adhesive for plywood. The above adhesive is tested for stability and applicability, applied to plywood, and performance tested.

[0092] Comparative Example 5

[0093] The preparation was carried out based on Example 4. The difference was that the monomer composition of the water-soluble acrylic resin was: 60% acrylic acid and 40% hydrophobic functional monomer methyl acrylate. The acrylic resin obtained by polymerization using this monomer composition was insoluble in water and could not be used for the next step.

[0094] Comparative Example 6

[0095] The formula and process are the same as those in Example 4, except that the hot pressing temperature is 150°C.

[0096] The test results of stability and application period of the formaldehyde-free adhesive for one-component plywood prepared in Examples 1 to 6 and Comparative Examples 1 to 6 are shown in Table 1 below.

[0097] Table 1 Summary of formaldehyde-free adhesive stability and application period test results

[0098]

[0099] Table 1 shows the results of the stability and pot life of the formaldehyde-free adhesive. From the above results, it can be seen that the one-component formaldehyde-free adhesive for plywood prepared by adding polyol curing agent in Examples 1 to 6 passed both the high temperature test and the room temperature test, and the pot life was ≥ 6 months, while Comparative Examples 1 to 2 were two-component adhesives, which gelled after 1 day of high temperature test and had a shorter pot life. Without being bound by any theory, this may be attributed to the fact that the activity of the polyol curing agent is inert at room temperature, can coexist with other components for a long time, and has a very long pot life.

[0100] The performance test results of the formaldehyde-free adhesives for one-component plywood prepared in Examples 1 to 6 and Comparative Examples 1 to 6 are shown in Table 2.

[0101] Table 2 Summary of formaldehyde-free adhesive properties

[0102]

[0103] Table 2 shows the performance test results of the formaldehyde-free adhesive. From the above results, it can be seen that no formaldehyde release was detected in the embodiment and comparative examples 1, 2, 3, 4, and 6, and the transfer rate was higher than 90%. Although the bonding strength of the embodiment is lower than that of comparative examples 1-2, it has a very long application period and can be made into a single component, which greatly improves the construction convenience of the glue. The bonding strength of comparative examples 3-4 is lower than that of the embodiment, and does not meet the requirement of bonding strength ≥ 0.7Mpa. It can be seen from comparative example 4 that if the content of the hydrophobic functional monomer is too low, even if the amount of curing agent is increased, the bonding strength is only limited. In addition, from the comparison results of Example 6 with Example 3 and Comparative Example 6, it can be found that when Example 6 uses β-hydroxyalkylamide as a curing agent, good bonding strength can still be obtained at a lower curing temperature, and the bonding strength is basically unaffected, while Comparative Example 6 using glycerol shows a lower bonding strength, and the strength decays more seriously after the temperature is lowered. Without being limited by any theory, it may be that β-hydroxyalkylamide has a lower curing temperature than ordinary polyols, and it also has a better cross-linking density at a lower curing temperature and has a more stable bonding strength.

[0104] The present application is described in detail above in conjunction with specific implementation methods and exemplary examples, but these descriptions cannot be understood as limiting the present application. Those skilled in the art understand that, without departing from the spirit and scope of the present application, a variety of equivalent replacements, modifications or improvements can be made to the technical solution of the present application and its implementation methods, all of which fall within the scope of the present application. The scope of protection of the present application shall be subject to the attached claims.

Claims

1. A formaldehyde-free adhesive for one-component plywood, characterized in that: The invention comprises a water-soluble acrylic resin, a filler, a thickener, a polyol curing agent and water, wherein the polyol curing agent is a compound containing at least two hydroxyl groups.

2. The one-component formaldehyde-free adhesive for plywood according to claim 1, characterized in that: Based on 100 parts by weight, the composition comprises 10 to 50 parts of a water-soluble acrylic resin, 5 to 40 parts of a filler, 0.5 to 5 parts of a thickener, 5 to 25 parts of a polyol curing agent and the balance of water.

3. The one-component formaldehyde-free adhesive for plywood according to claim 1, characterized in that: The polyol curing agent is β-hydroxyalkylamide, 1,2-ethylene glycol, 1,3-propylene glycol, diethylene glycol, 1,4-butylene glycol, 1,2,3-cyclohexanetriol, 1,2,4-butylene glycol, 1,2,3-butylene glycol, 1,2,5-pentanetriol, glycerol, glycerol polyether polyol, 2,2-dimethyl-1,3-propylene glycol, 2-butyl-2-ethyl-1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2-methyl-2,4-butylene glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 2-ethyl-1,3-hexanediol, 2-hydroxymethyl-2-methyl-1,3-propylene glycol, 2-ethyl 1,2-propylene glycol, 1,2-propylene glycol dimer, 1,2-propylene glycol trimer, ethanolamine, isopropanolamine, diethanolamine, diisopropanolamine, triethanolamine, a homopolymer of hydroxyethyl (meth)acrylate, a copolymer of hydroxyethyl (meth)acrylate, a homopolymer of hydroxypropyl (meth)acrylate, a copolymer of hydroxypropyl (meth)acrylate, or polyvinyl alcohol.

4. The one-component formaldehyde-free adhesive for plywood according to claim 3, characterized in that: The β-hydroxyalkylamide is shown in Formula I: Wherein, R is methyl or hydrogen, and m=2-8.

5. The one-component formaldehyde-free adhesive for plywood according to claim 1, characterized in that: The water-soluble acrylic resin is a water-based high molecular polymer obtained by solution polymerization of a vinyl-containing unsaturated carboxylic acid monomer and a hydrophobic functional monomer in an aqueous solution. No emulsifier is added to the water-soluble acrylic resin. The water-soluble acrylic resin has a molecular size of ≤1nm, a number average molecular weight of 2000-30000, and the content of the hydrophobic functional monomer is 10-35% of the content of the water-soluble acrylic resin monomer.

6. The one-component formaldehyde-free adhesive for plywood according to claim 1, characterized in that: The filler is selected from one or more of bentonite, calcined kaolin, washed kaolin, calcium sulfate, talc, zeolite, mica powder, attapulgite, barium sulfate, quartz powder, and fumed silica; the thickener is selected from one of anionic polyacrylamide thickeners, lithium magnesium silicate, xanthan gum, hydroxyethyl cellulose ether thickeners, sodium alginate, guar gum, bentonite, and polyurethane.

7. A one-component formaldehyde-free adhesive for plywood according to any one of claims 1 to 6, characterized in that: The formaldehyde-free adhesive for the one-component plywood has a bonding strength of ≥0.7 MPa.

8. A one-component formaldehyde-free adhesive for plywood according to any one of claims 1 to 6, characterized in that: The formaldehyde-free adhesive for one-component plywood has an applicability period of ≥6 months and an open time of ≥6 hours.

9. A one-component formaldehyde-free adhesive for plywood according to any one of claims 1 to 6, characterized in that: The formaldehyde-free adhesive for one-component plywood has a transfer rate of ≥90%.

10. Use of the one-component formaldehyde-free adhesive for plywood according to any one of claims 1 to 9 in the preparation of plywood.

Citation Information

Patent Citations

  • Formaldehyde free adhesive composition

    CN111918945A